Load-carrying capacity of timber-to-timber joints of fast-growing Argentinean Eucalyptus grandis with nails of small diameter laterally loaded in double shear. Analysis according to the criterion adopted by European standards - Piter, Juan Carlos Jesús (2013)
The present paper reports the results of an investigation regarding the study of the load-carrying capacity of connections with nails of small diameter pneumatically driven in timber-to-timber joints of fast-growing Argentinean Eucalyptus grandis. The effectiveness of the equations provided by the Eurocode 5 (EN 1995-1-1 2005) for calculating the lateral load-carrying capacity of these joints was checked for the specimens exhibiting the geometrical parameters adopted by the European design rule and also for those with reduced spacing and end distances. A failure mode presenting features common to both j and k types of failure according to the criterion of the European design rule confirmed that the plastic hinges could be developed before brittle failure due to splitting or block shear occurred, even if the specimens present reduced spacing and end distances. The load-slip curves confirmed ductile behaviour for all cases. The empirical results showed that the structural design is situated on the conservative side if the equations adopted by the Eurocode 5 (EN 1995-1-1 2005) are applied to the analysed connections when the spacing and end distances recommended by this design rule are used. The results also showed that the joint area may be decreased up to 31% in relation to that corresponding to the recommended spacing and end distances without reducing the load-bearing capacity below the characteristic value determined according to the European design rule.